Peningkatan Ekonomi Masyarakat Berbasis Sumber Daya di Desa Plupuh Kabupaten Sragen - Pardosi, Victor Benny Alexsius; Sumboro, Budhi; Koes, Agung (Edujavare Publishing, 2025)
Community service activities include mentoring MSMEs in business licensing, simple financial management training, and utilizing digital technology for product marketing. This community service program aims to increase the competitiveness of MSMEs and strengthen the local economy based on available resources. This community service method uses Participation Action Research (PAR), with a qualitative descriptive approach with participatory-based implementation in helping to develop the potential of Plupuh Village, Plupuh District, Sragen Regency. The results of the community service show that community service activities are running smoothly with the main strategy for developing MSMEs in Plupuh Village including strengthening institutions, increasing human resource capacity, and utilizing digital technology. Digitalization of MSMEs has proven to be an effective solution in facing increasingly tight market competition. Strengthening partnerships with the government, private sector, and universities is also important to support the sustainability of MSMEs. This partnership can provide wider access to resources, funding, and technical guidance needed to increase the competitiveness of local products. The expected results of this community service program can be a reference for the development of community-based economic models in other similar areas.